2019
DOI: 10.1002/hed.25736
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends for upper aerodigestive tract cancers in rural United States counties

Abstract: Background Recent declines in cancer incidence and mortality have not been distributed equally across the United States. Factors such as tobacco cessation and human papillomavirus presence might differentially affect urban and rural portions of the country. Methods We used the Surveillance, Epidemiology, and End Results database to assess cancer incidence rates and trends from 1973 to 2015. We compared incidence rates for oral cavity, oropharynx, and larynx cancer in urban and rural counties and identified tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…The incidence rates for HNC and the rate of death among all HNC patients have both declined somewhat in recent years 16,25 . Yet, in a SEER database study, the incidence of oropharynx cancer was shown to be increasing faster in rural areas, while the rates of larynx and oral cavity cancers were decreasing more rapidly in urban areas 26 …”
Section: Hnc Outcomes and The “Rural Disadvantage”mentioning
confidence: 99%
“…The incidence rates for HNC and the rate of death among all HNC patients have both declined somewhat in recent years 16,25 . Yet, in a SEER database study, the incidence of oropharynx cancer was shown to be increasing faster in rural areas, while the rates of larynx and oral cavity cancers were decreasing more rapidly in urban areas 26 …”
Section: Hnc Outcomes and The “Rural Disadvantage”mentioning
confidence: 99%
“…For a long time, there is no well-established vision-based method for oral cancer detection. The diagnosis of OCSCC has to rely on invasive oral biopsy which is not only time-consuming, but also not guaranteed in primary care or community settings, especially in developing countries [ 9 , 10 ]. Thus, quite often OCSCC patients cannot receive timely diagnosis and referrals [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively, they are the seventh most common cancer worldwide and the ninth most common cancer in the United States 2 . The vast majority are squamous cell carcinomas (SCC), with major risk factors including alcohol consumption, tobacco usage, human papillomavirus (HPV) infection, male gender, and older age 2,3 . Estimates of 5‐year survival for patients with HNC vary based on prognostic factors that include stage at initial diagnosis and age at diagnosis 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in survival for patients with HNC have been well documented in literature, and include race, 6–8 socioeconomic status of patient, 8–12 as well as the overall socioeconomic status of the neighborhood in which the patient resides 8,13 . These factors contribute to disparities on multiple levels of the care continuum, associated with altered rates of offering smoking cessation (primary prevention), 3,14 frequency of HNC examinations (secondary prevention), 14 treatment offered and received by patients, and time to treatment initiation 15,16 . Therefore, it is not surprising that these marginalized populations are often presenting with more advanced stage of cancer and may have poorer prognoses 8,16,17 …”
Section: Introductionmentioning
confidence: 99%